To be or not to be catholic in Latin America. The actual dilemma - Quesada Chaves, Marco Antonio (2018)
The situation of the religious subject in Latin America shown by two important studies such as the Pew Research Center and the Latinobarómetro; both carried out in 2014, denote a series of important transformations in the way this subject is understood, assumed and lived by the majority of Latin Americans. There is a decrease in the number of people who identify themselves as Catholics, in turn there is a growing number of Protestants, and a third group that does not have any religious affiliation, but which is still religious. From a historical-theological perspective, the present article discusses two phenomena that are found in the present situation: that of secularization from the Latin American reality, and that of the so-called "cultural Catholics"; a complex phenomenon, paradoxical as well as challenging.